Multiple problems: a case of Cohen syndrome VPS13B mutation causing bilateral spherical lenses combined with retinitis pigmentosa - Yifan Wang; Keqing Meng; Hong Chen; Xin Jin; Guoxing Yang; Gaoyang Ma; Yu Cheng; Chenyu Zhao; Congcong Zheng; Ming Xie; Pengju Gao; Lifei Wang; et al. (BMC Ophthalmology)
Abstract Background Cohen syndrome is a rare autosomal recessive disorder characterized by facial anomalies with or without microcephaly, non-progressive intellectual disability, hypotonia, ocular abnormalities, and neutropenia. Due to its low prevalence and diverse presentations, much information about the disease, including ocular manifestations, is not yet fully understood. To date, there is a paucity of literature on Cohen syndrome, which is characterized by predominantly ocular manifestations and typical manifestations in multiple systems throughout the body. Case presentation A 24-year-old male with a history of intellectual disability since childhood presented with decreased vision in both eyes for 2 years. He was diagnosed with bilateral spherical lens, bilateral subluxation of lens, bilateral concurrent cataracts, and bilateral retinitis pigmentosa. Cataract extraction combined with intraocular lens implantation was successful in both eyes, and vision improved after surgery. His underlying syndrome was studied genetically by whole exome sequencing. Genetic testing through whole-exome sequencing revealed a mutation in the VPS13B gene: c.6865 + 1G > T, confirming the diagnosis of Cohen syndrome. Conclusion Ophthalmologists should consider the diagnosis of Cohen syndrome in patients with developmental delay, spherical lens, and retinitis pigmentosa. A detailed ophthalmologic examination and general examination should be considered in such patients.